DEVELOPMENT OF THE PAGARALAM COLLEGE OF TECHNOLOGY OF COMPUTER NETWORK TO ACCOMMODATE DIGITAL CAMPUS - Dedi Setiadi; Dedy Syamsuar (Jurnal TAM (Technology Acceptance Model), 2021)
The use of information and communication technology is very important in supporting all daily human activities. In the world of education, information and communication technology has a very important role or benefit because many activities in the world of education take advantage of this technology. Pagaralam College of Technology is one of the colleges utilizing information and communication technology, computer networks, but the existing network conditions are not optimal so that the quality needs to be improved to make it better. Also with the increasing competition in higher education management, it is very important for a college to think about how the institution can survive and be superior in determining its competitiveness with other colleges so that the digitization of the campus or the creation of a digital campus is one of the strategies that must be implemented in the face of development existing information and communication technology. This study aims to improve the quality of computer networks to prepare the Pagaralam College of Technology to accommodate the need to become a digital campus, using SWOT analysis methods and TopDown Network Design, network quality testing, or Quality of Service (QoS), and development methods using PPDIOO. (Prepare, Plan, Design, Implement, Operate, Optimize). This research results in a better or more reliable new computer network design or blueprints to realize or accommodate a digital campus.